Expression and significance of molecular profiles on eosinophils of children with food allergy. (August 2019) - Ding, Junqiong; Hou, Jia; Liu, Danru; Wang, Ying; Wang, Xiaoming; Wang, Xiaochuan
Peripheral blood eosinophils may increase in food allergy (FA). However, the correlation between activation status of blood eosinophils and features of FA are unknown. We collected 25 cases of FA out-patients with increased number of eosinophils and 20 healthy children. Eosinophil surface markers were analyzed by flow cytometry. We found that CD23, CD44, CD54, and CRTH2 were positive on different eosinophils and that their expressions were increased in FA patients compared to the control individuals. There was a positive correlation with strong protein–protein interactions between the four eosinophil surface markers which were functionally involved in regulation of cell killing, interferon-gamma-mediated signaling pathway, and Epstein–Barr virus infection pathway. Thus, blood eosinophils change their phenotype during FA and induce significant gene regulation changes that may cause FA with eosinophilia. Detection of the expression of CD23, CD44, CD54, and CRTH2 on eosinophils can be used as indicators of FA with eosinophilia.